(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to investigate the accuracy and reliability of an electronic apex locator integrated into the Ai-Motor endodontic motor when used on transparent 3D-printed teeth in a chlorhexidine solution environment. Methods: Three extracted human premolars obtained from patients indicated for orthodontic extraction were scanned using cone-beam computed tomography (CBCT). Based on these datasets, ten transparent 3D-printed tooth models were designed and fabricated, with access cavities pre-prepared using dedicated software. The printed teeth were placed in a transparent container filled with chlorhexidine solution and fixed on the specimen stage of an optical microscope. A WaveOne Gold instrument (Dentsply Sirona, Maillefer, Switzerland) mounted on the handpiece of the Ai-Motor was rigidly fixed to a separate microscope stage and introduced into the root canal to locate the apical foramen under two operating modes: automatic stop at the apex and automatic reverse rotation upon reaching the apex. Changes in the position of the microscope’s fine micrometer knob between measurements were recorded and compared. Agreement between the two apex localization modes was assessed using Bland–Altman analysis. Results: Both operating modes demonstrated a high level of agreement, with no evidence of fixed or proportional bias. The presence of chlorhexidine solution did not adversely affect the accuracy of apex localization. Conclusion: The electronic apex locator integrated into the Ai-Motor endodontic motor provides accurate and reliable apical foramen determination on transparent 3D-printed teeth in a chlorhexidine solution environment.